PENGARUH PENGELOLAAN SUMBER DAYA DALAM ISO 9001:2008 TERHADAP KINERJA KARYAWAN (Studi pada PT. Indofood CBP Sukses Makmur Tbk Semarang) - Ghea Ayunda Primasetya; Wahyu Hidayat; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
In order to keep the existence and continuity of a company, surely in its operations, the company needs to focus on the customer under the terms demanded by customers internally and externally in terms of customers' satisfaction. Relating to the quality aspects, a standardization of the management is required in order to maintain company's performance to produces quality products and services, and increase the productivity of the company in an efficient manner, namely ISO 9001: 2008. One of the companies that implement ISO 9001: 2008 is PT. Indofood CBP Sukses Makmur Tbk Semarang. Employees' performance data of PT. Indofood is fluctuating so it needs to be re-assess through this research. This research aims to determine the effect of training, working environment, and infrastructure towards employee performance at PT. Indofood CBP Sukses Makmur Tbk Semarang. Data collecting methods used in this research was probability sampling with 109 employees as data samples. Datas analysis were quantitative analysis using SPSS program version of 17.0. The analysis method used were correlation test, determination, simple linear regression, multiple linear regression, T-test and F-test. The results of the research showed that there are positive and significant effects between training, working environment, and infrastructure towards employee performance at PT. Indofood CBP Sukses Makmur Tbk Semarang either partially or simultaneously. Variable training has the highest effect towards employee performance in PT. Indofood CBP Sukses Makmur Tbk Semarang compared to working environment and infrastructure. Training can be enhanced by increasing internal training conduciveness and additional facilities. Working environment can be improved by rearranging the layout of employees’ room. In addition, the infrastructure can be improved by increasing the availability of technology and a special user guidance of technology provided by the company formally.